Rynek wyrobów cukierniczych i kształtujące się na nim tendencje zmian asortymentowych - Antkowicz, Anna (Confectionary Market and the Tendencies which Form the Range of Products, 2006)
In the presented article the issue connected with necessity of adjusting confectionary products to customers' needs is raised due to many changes taking place in Polish society's eating habits. Confectionary enterprises modify the range of products they offer by introducing products of different kind, for example products with reduced amount of sugar, fat and products enriched with vitamins or specific ingredients like nuts. This is the way in which confectionary companies react for increasing obesity and overweight problem and the problem of aging society. It has been proved that functional food is becoming more and more popular and people are buying this kind of food much more eagerly. Therefore, investing in this kind of company and their products should become a challenge for every company in this field of production.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 25-30